Uji Stabilitas dan Aktivitas Sediaan Patch Herbal Anti-Acne Ekstrak Etanol Daun Gaharu - Simanullang, Gayatri; Ramadhani, Untia Kartika Sari; Suprahman, Nisa Yulianti; Maretta, Gres; Syafitri, Dewi Rana; Saeli, Pinka Mustika; Ashafila, Tsalsha (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Acne is a skin condition characterized by the formation of skin bumps due to bacterial activity. Secondary metabolite compounds found in Gaharu leaves, such as flavonoids known for their antibacterial properties. This research aims to assess the physical and chemical stability of an anti-acne patch containing ethanol extract from Gaharu leaves and chitosan polymer. Additionally, this research aims to evaluate the antibacterial effectiveness of the anti-acne patch against Propionibacterium acnes. The experimental approach involves stability testing through cycling tests, observation of physical and chemical properties before and after stability tests, and antibacterial activity testing against P. acnes. The results from the stability test indicate overall stability in organoleptic aspects, thickness, folding ability, weight consistency, moisture content, vapor transmission, and moisture absorption of the anti-acne patch. However, instability is noted in the pH of the preparation. The antibacterial activity test reveals that the entire formulation exhibits antibacterial properties against P. acnes. Furthermore, there is a positive correlation between the increased concentration of ethanol extract from Gaharu leaves or chitosan polymer and the heightened barrier zone value.